Reverse-flow anterolateral thigh flap for knee soft-tissue reconstruction: case report - R., Banegas-Ruíz; Fabián, Gómez-Mendoza Francisco; Rubén, Baca-Domínguez Carlos; Gerardo, Campos-Angulo; Alejo-Fuentes, Luis Jesús; Alejo-Fuentes, Luis Fernando; Christian, Porras-Méndez; AI, Valderrama-Treviño; Espinosa-Torres, Juan Pablo; Mendoza-Barrera, Germán E.; Rafael, Escalera-Moreno; Berenice, Yañez-Roa; et al. (International Journal of Research in Medical Sciences, 2019)
The reconstruction of the injured tissue around the knee is a complex procedure for the plastic and orthopaedic surgeon. The objective is to provide an acceptable function and aesthetic result. Successful wound management includes meticulous debridement, planning and proper execution of the surgical procedure. An 11-year-old male patient with a right patellar fracture using an anterolateral thigh flap with reverse flow to cover the skin defect. For such purposes, the reverse flow anterolateral flap is an effective, trustworthy and well-documented option. The correct obtaining and implantation of the flap reduces the morbidity of the donor site, offers options in size and design, an adequate length of the pedicle and the possible combination with the fascia lata in case it is required. The versatility of the reverse flow anterolateral flap makes it a possible therapeutic alternative in reconstructive surgery since it is aesthetic and functional for the reconstruction of tissue near the knee joint.